Evaluating The Digital Performance and Accessibility of IIT Library Websites Using Google Lighthouse - Dubey, Vikrant; Verma, Shilpi (International Journal of Computer Sciences and Engineering, 2025)
This study presents a comprehensive performance analysis of the library websites of 23 Indian Institutes of Technology (IITs) using the Lighthouse tool. IIT libraries are essential information hubs that support the academic and research needs of students, faculty, and external researchers. To assess the digital performance of these websites, Lighthouse, a popular open-source tool by Google, was employed to evaluate key metrics such as performance, accessibility, best practices, and SEO. The analysis revealed significant variation in the quality of IIT library websites, with top performers like IIT Indore and IIT Mandi excelling in performance and accessibility. At the same time, IIT Tirupati and IIT (BHU) Varanasi lagged behind, especially in terms of loading speed and adherence to best practices. The study highlights areas for improvement, such as optimizing resource management, enhancing accessibility for users with disabilities, and improving search engine optimization (SEO) to increase discoverability. Actionable recommendations help IIT libraries improve their digital presence, ensuring a more efficient, accessible, and user-friendly user experience.